A Uremic Stomatitis in Patient with Chronic Kidney Disease on Hemodialysis at RSUD Prof. Dr. Margono Soekarjo - Evi Triviana Sufyaning Rahayu; FERINA AYU MAHARANI HAIBAR; Twasi Anilamaba; Rinawati Satrio; Wahyu Djatmiko (Journal of Indonesian Dental Association, 2026)
Introduction: Chronic Kidney Disease (CKD) is a condition of slow and irreversible decline in kidney function, leading to the accumulation of metabolic waste products such as urea and creatinine. The buildup of these toxins can trigger systemic manifestations, including oral lesions such as uremic stomatitis. Although often overlooked, these oral manifestations can reduce patients’ quality of life and nutritional status due to pain during eating. Case Report: A 63-year-old female patient diagnosed with Chronic Kidney Disease (CKD) was admitted to Prof. Dr. Margono Soekarjo Regional General Hospital. Laboratory tests revealed elevated levels of urea, creatinine, and potassium, as well as decreased hemoglobin and hematocrit, indicating the presence of anemia and hyperkalemia. An intraoral examination revealed an ulcerative lesion on the right lateral aspect of the tongue with a grayish-white base and a purplish hemorrhagic lesion on the base of the tongue, accompanied by pain during eating. The diagnosis was established as uremic stomatitis based on subjective and objective examinations, as well as a complete blood count. Management included systemic therapy and oral care using 0.2% chlorhexidine gluconate and Candistatin drops. Conclusion: Chronic kidney disease can trigger the appearance of uremic stomatitis in the oral cavity. Therefore, clinical examination of the oral cavity is essential for the early identification of systemic disorders while supportive management and oral hygiene education can help prevent complications and improve the comfort and quality of life of CKD patients.